2020
DOI: 10.1101/2020.04.27.063578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic examination of preprint platforms for use in the medical and biomedical sciences setting

Abstract: ObjectivesThe objective of this review is to identify all preprint platforms with biomedical and medical scope and to compare and contrast the key characteristics and policies of these platforms. We also aim to provide a searchable database to enable relevant stakeholders to compare between platforms. Study Design and SettingPreprint platforms that were launched up to 25 th June 2019 and have a biomedical and medical scope according to MEDLINE's journal selection criteria were identified using existing lists, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 11 publications
0
42
0
1
Order By: Relevance
“…The large-scale use of preprints is a novel development for the biomedical sciences [13], and new mechanisms to manage this evidence dissemination track need to be invented. The algorithm designed for the present study offers such a mechanism by detecting the appearance of new evidence sources in real-time and summarizing this information in a web interface [14].…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…The large-scale use of preprints is a novel development for the biomedical sciences [13], and new mechanisms to manage this evidence dissemination track need to be invented. The algorithm designed for the present study offers such a mechanism by detecting the appearance of new evidence sources in real-time and summarizing this information in a web interface [14].…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 7, 2020. ; https://doi.org/10.1101/2020.09.04.20188771 doi: medRxiv preprint in the vetting process (Kirkham et al, 2020). Although not to be mistaken for a formal pre-ppr, it does indicate that most biomedical preprints vet preprints for quality-control before officially make manuscripts available on their repositories.…”
Section: Competition and Epistemic Oversupplymentioning
confidence: 99%
“…The studies will be written up for publication in open-access, peer-reviewed journals, prioritising outlets which will facilitate a speedy publication timeframe. Preprint versions of the manuscripts will be posted on public preprint servers ( Kirkham et al , 2020 ) before formal publication in scholarly journals. Relevant reporting guidelines will be utilised to ensure the completeness and transparency of the articles; specifically, findings from WP1 will be reported in line with the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) Statement ( von Elm et al , 2008 ), and findings from WP2 will be reported in line with the COnsolidated criteria for REporting Qualitative research (COREQ) checklist ( Tong et al , 2007 ).…”
Section: Protocolmentioning
confidence: 99%